Socio-philosophical analysis of terrorism as a manifestation of war - Yushina, Svetlana V. (Opción, 2019)
The research objective is to investigate terrorism as a contemporary phenomenon, to identify the main generic features and distinctive characteristics of war and terrorism as a social destructive phenomenon. The methodology included the systemic and activity approaches, and the comparative analysis of generic concepts of war and terrorism. The concepts of foreign and Russian theoreticians are presented, who studied terrorist war in three directions: civilizational, military-political and informational. The author formulates the definition of modern terrorism and comes to the conclusion that terrorism is a form of warfare, yet these two phenomena have substantial differences.